Implementing front-of-pack nutrition warning labels in Mexico: important lessons for low- and middle-income countries - Eric Crosbie; Margarita Gabriela Otero Alvarez; Michelle Cao; Lesly Samara Vejar Renteria; Estefania Rodriguez; Ana Larrañaga Flota; Angela Carriedo (Cambridge University Press, 2023)
Abstract Objective: To analyse the implementation of front-of-pack nutrition labelling (FOPNL) in Mexico. Design: Review of publicly accessible documents, including legislative websites, news sources, and government, intergovernmental, and advocacy reports. Usage of the policy cycle model to analyse the implementation and evaluation stages of Mexico's General Health Law, amended with FOPNL (2019-2022). Results: In October 2019, the government published a draft modification of the Norma Oficial Mexicana (Official Mexican Standard) to regulate and enforce a new FOPNL warning label system. A 60-d public consultation period followed (October-December 2019), and the regulation was published in March 2020 and implementation began in October 2020. An analysis of nine key provisions of the Standard revealed that the food and beverage industry and its allies weakened some original provisions including health claims, warnings for added sweeteners and display areas. On the other hand, local and international public health groups maintained key regulations including the ban on cartoon character advertisements, standardised portions and nutrient criteria following international best practices. Early implementation appears to have high compliance and helped contribute to reformulating unhealthy products. Continued barriers to implementation include industry efforts to create double fronts and market their cartoon characters on social media and through digitalised marketing. Conclusion: Early success in implementing the new FOPNL system in Mexico was the result of an inclusive and participatory regulatory process dedicated to maintaining public health advances, local and international health advocacy support, and continued monitoring. Other countries proposing and enacting FOPNL should learn from the Mexican experience to maintain scientifically proven best practices, counter industry barriers and minimise delays in implementation.